2010
DOI: 10.1093/rpd/ncq417
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of counting efficiencies of a whole-body counter using Monte Carlo simulation with voxel phantoms

Abstract: In the 2007 recommendations of the International Commission on Radiological Protection, it is mentioned that the reference voxel phantoms are used for calculation of effective dose. From the standpoint of internal dosimetry services, calibration methods of whole-body counters using the voxel phantoms are of considerable practical interest. In the present study, counting efficiencies of a whole-body counter at the Japan Atomic Energy Agency (JAEA) were evaluated using Monte Carlo simulations with two voxel phan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…But this level of accuracy is not that relevant considering the uncertainties related to a mispositioning of the phantom itself. While some authors consider them 'significant tools' for the calibration of WBC (35) , others believe that 'for in vivo counting in the context of radiation protection, efficiencies can be deduced with sufficient accuracy from measurements or simulations of simple phantoms' (5) . Guardini and Ferrari (10) argue that the accuracy in geometry representation improved by voxel models is only one contributor to the overall accuracy of a WBC measurement and not the most important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But this level of accuracy is not that relevant considering the uncertainties related to a mispositioning of the phantom itself. While some authors consider them 'significant tools' for the calibration of WBC (35) , others believe that 'for in vivo counting in the context of radiation protection, efficiencies can be deduced with sufficient accuracy from measurements or simulations of simple phantoms' (5) . Guardini and Ferrari (10) argue that the accuracy in geometry representation improved by voxel models is only one contributor to the overall accuracy of a WBC measurement and not the most important.…”
Section: Discussionmentioning
confidence: 99%
“…Various MC computer codes have been used so far: 'FLUktuierende KAskade' (FLUKA) (25) , 'Monte Carlo N-Particle' (MCNP) (26 -33) , 'Electron Gamma Shower' (EGS) (5,6,34,35) , 'PENetration and Energy LOss of Positrons and Electrons' (PENELOPE) (32) , 'GEometry ANd Tracking' (GEANT) (36) or local codes developed ad hoc (37) . MC calculation has been used to compare different mathematical phantoms used in WBCs (10,26,27,29,31,35,38) or to compare the measurements obtained with a physical phantom with the results obtained by a simulated version of this phantom (5,6,30,35,37) . MC calculations are also used to investigate how the counting efficiency of the WCB depends on various parameters of the system that may be sources of uncertainty, such as the difference between the shape and size of the person to be monitored and the phantom, the measuring geometry, notably the position of the detector, the phantomdetector distance, the distribution of the radionuclides in the body, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that it was difficult to develop these phantoms with the FFD algorithm and the internal organs are not adjusted to age-dependent values. The Otoko phantom was recently used in a study to calculate dose conversion coefficients for the Japanese population (Takahashi et al 2011). …”
Section: The Evolution Of Computational Phantomsmentioning
confidence: 99%
“…The authors reported that it was difficult to develop these phantoms with the FFD algorithm and the internal organs are not adjusted to agedependent values. The Otoko phantom was recently used in a study to calculate dose conversion coefficients for the Japanese population [80].…”
Section: Second-generation Voxel Phantoms (From Late 1980 To Early 20mentioning
confidence: 99%